Ethics in crisis situations - Fernández Arce, César (2009)
Peru, as many other countries, goes through a crisis of moral values which have been disrupted by material ones estimated in terms of utility, convenience or personal benefit; not even those prevalent human rights have prevented such disruption. Thus, it is urgent to revalue those rights since they are an essential requirement for human dignity. Likewise, it is necessary to take into account that economic growth is vital but not sufficient. Besides, it is necessary to count with the people’s ethical growth and the institutions’ strengthening on this regard; otherwise, it will be senseless to state that a human being is an end for himself